DIPHTHERIA AS A SYSTEMIC DISEASE: ANALYSIS OF COMPLICATIONS ASSOCIATED WITH DIPHTHERIA TOXIN - Patrycja Jędrzejewska-Rzezak; Monika Czekalska; Natalia Kulicka; Kinga Knutelska; Aleksandra Winsyk; Paulina Gajniak; Maciej Karwat; Tytus Tyralik; Klaudia Bilińska; Joanna Węgrzecka (International Journal of Innovative Technologies in Social Science, 2025)
Diphtheria is a contagious disease caused by the bacteria Corynebacterium diphtheriae. This disease, although morbidity has significantly decreased in developed nations thanks to immunizations, continues to provide a substantial health risk in areas with low immunization rates. Diphtheria, with the acute inflammatory phase of the upper respiratory tract, can result in severe organ problems, mainly due to the effects of diphtheria toxin. Cardiac involvement, manifested as myocarditis, constitutes the most severe consequence of diphtheria and is the primary cause of mortality in affected persons. Diphtheritic polyneuropathy represents a considerable portion of post-diphtheritic sequelae and has a positive prognosis; therefore, timely diagnosis is crucial for efficient treatment. Renal impairment in diphtheria is less commonly reported than cardiac and neurological sequelae, necessitating greater investigation in this domain. This article reviews the current knowledge on the mechanisms of action of diphtheria toxin, the epidemiology of complications, their clinical manifestations, and possible diagnostic and therapeutic strategies. The significance of prophylaxis and the increasing danger of illness recurrence due to diminishing vaccination rates in some communities was also emphasized. Aim of the study: This article aims to elucidate the current state of knowledge on organ complications of diphtheria, focusing on the mechanisms of diphtheria toxin, prevalent clinical manifestations, and potential implications in the cardiovascular, neurological, and renal systems. The paper seeks to highlight the significance of early diagnosis and underscore the need for a multidisciplinary approach in the management of respiratory diphtheria. Materials and methods: A review of the literature available in the PubMed and Google Scholar database was performed, using the key words: „diphtheria”, „cardiac complications”, „neurological complications”, „myocarditis”, „polyneuropathy”, „Corynebacterium diphtheriae”.